PENGARUH PROMOSI TERHADAP PERILAKU BELI KONSUMEN PADA PRODUK TATA RIAS WAJAH - Putri Komala Sari; Linda Rosalina (Universitas Negeri Padang, 2022)
The promotion of company (La Tulipe Cosmetique) by a joint sponsorship with the famous MUA is Influences to college student behavior in buying make-up products. It is seen that college student bought is driven by psychological because the product is used by favorite MUAs. This reseacrh was conducted to know the Influence of promotion on consumer buying behavior in make-up products. This research is a quantitative descriptive chorelational type. Population in this research, students of the Department Make-up and Beauty 2017, 2018, 2019 with a total of 331 peoples. Sample in this research is 77 peoples, that taken by proportional random sampling technique and the Slovin formula. Data were collected by a questionnaire with 42 questions which were processed using the validity test, reliability test. Descriptive data analysis was obtained from percentage formula, hypothesis testing using Pearson correlation product moment and t test. The test results prove that promotion of company (La Tulipe Cosmetiques) has a strong relations with consumer buying behavior with a correlation score of the Pearson correlation product moment (r) of 0.602. The hypothesis Ha is accepted with a significance level of 95% because t count> t table (8,617> 2,000).